Morphometric variations of stingless bees in southern kerala and assessment of honey quality - Divya K K (Department of agricultural entomology, College of agriculture, 2016)
The investigation entitled "Morphometric variations of stingless bees in southern Kerala and assessment of honey quality " was conducted at College of Agriculture, Vellayani during 2013-15 with the objective to study the morphometric variations among stingless bee populations, their documentation and to evaluate the physical, chemical and antioxidant properties of their honey. A purposive sampling was conducted in the bee keeping pockets of upland and midland physiographic regions of southern Kerala from where ten stingless bee workers and one honey sample were collected from fifteen locations of each physiographic region. The nest architecture and foraging plants were also recorded at the time of sample collection. Studies on the design of hive entrance revealed that out of thirty locations, slit like (elliptical) nest entrance was maximum (22), when compared to the round (6) and multiple entrance (2). The stingless bee hive at midland location, Pullampara had the maximum hive entrance width (>2 cm) and number of guard bees (20). Considering the length of hive entrance, maximum number of colonies were observed under the category 1-3 cm length and maximum number of colonies (14) were placed at a height of > 2 metre category from the ground level. Bee wax, plant resins, dry leaves and vegetative parts, wood particles, bee cadavers, sand and soil particles were used by stingless bees for construction of their nest entrance. Fifty foraging plants were visited by stingless bees, of which 14 plants were categorized as pollen providers, 14 as nectar providers and 22 as both nectar and pollen providers. Studies on morphometric parameters within the locations revealed that proboscis length (1.502 mm), femur length (0.918 mm), length (0.480 mm) and width (0.257 mm) of metatarsus, length (3.284 mm) and width (1.183 mm) of forewing in stingless bees recorded from the midland location, Malayam were significantly different from rest of the samples. The morphometric parameters viz. length of proboscis (1.049 mm), length (2.854 mm) and width (1.056) of stingless bee forewing, femur length (0.782 mm), metatarsus length (0.404 mm) and third sternite width (1.148 mm) obtained from midland were found to be statistically superior to the upland samples. Studies on physico-chemical and antioxidant properties of stingless bee honey showed that the parameters viz., pH (3.45), EC (20.16 µS/cm), total dissolved solids (29.85 ppm), colour intensity (880.57 mAU), reducing sugar (69.96 per cent), flavanoids (220.09 mg catechin /kg), total poly phenols (879.84 mg catechol/ kg), diastase (31.20 Diastase Number (DN)), invertase activity (136.15 Invertase Number (IN)) and antioxidant content (374.84 μM Fe II/100 g) of the honey samples collected from upland was statistically superior to midland whereas the moisture content (20.45 %) recorded from midland was significantly higher than the upland. The population of bacteria and fungi recorded from the stingless bee honey samples were found within the admissible levels while actinomycetes were absent in all honey samples. From the study it was inferred that the stingless bees preferred slit like entrance and the hive entrance was found to be constructed with similar materials irrespective of the locations. Significant variations in morphometric parameters which determine the pollinator efficiency were observed between midland and upland locations. The stingless bee honey quality parameters were superior to the suggested quality standards in terms of moisture content, reducing and non reducing sugars and diastase activity.